An OB-fold complex controls the repair pathways for DNA double-strand breaks - Shengxian Gao (Nature Portfolio, 2018)
How repair pathway selection occurs is still a matter of debate and many factors have been associated to this function. Here the authors provide insight into the role of FAM35A and C20ORF196, two REV7-interacting proteins, which are recruited at double-strand breaks to promote non-homologous end joining repair.